Spirulina platensis effect on oxidative stress of rat’s offspring brain exposed to cigarette smoke during pregnancy and lactation - Kenny Cantika Abadi; Febriana Catur Iswanti; Sri Widia A Jusman; Fadilah Fadilah; Ani Retno Prijanti (Acta Biochimica Indonesiana)
Background: Maternal exposure to cigarette smoke during pregnancy and lactation might harmful for the fetus. The smoke contains many free radicals that could be eliminated by antioxidant. This study aimed to investigate the effect of Spirulina platensis ethanol extract as antioxidant against cigarette smoke exposure during pregnancy until lactation by assessing oxidative stress markers in neonatal brain tissues.